Peran Kepercayaan dalam Mengurangi Tingkat Stres di Kalangan Pasangan Suami Istri - Hosea, Helena Andriani; Ng, Cheryl Alvira; Lee, Vivian; Marpaung, Winida; Putra, Achmad Irvan Dwi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to examine the relationship between trust and stress levels in married couples. The study sample consisted of 187 husbands and wives in Titi Kuning Village, selected using purposive sampling, considering the characteristics of respondents who are married and living together as the unit of analysis relevant to the research objectives. Of these, 181 respondents met the assumption of data normality and were subsequently analyzed. Measurements of trust and stress levels were carried out using psychological scales that have been tested for validity and reliability, each consisting of 39 and 40 items. Data analysis used the Pearson Product Moment correlation method after all analytical assumptions, including normality and linearity, were met. The findings indicate a significant negative relationship between trust and stress levels, with a correlation coefficient of -0.603 and a significance value of 0.000 (p < 0.05). The result concludes that higher trust are associated with lower stress levels, and conversely, lower trust are correspond with higher stress levels among married couples in Titi Kuning Sub-District. The effective contribution of trust to stress, with an R-squared value of 0.364, indicates that increased trust between husband and wife contributes to reduced stress levels. Thus, trust contributes 36.4% to stress levels, with the remaining 63.6% influenced by other factors. These findings provide a theoretical contribution to the development of marital psychology studies by highlighting the role of trust as a significant psychological factor in managing marital stress. Practically, these findings suggest the importance of strengthening trust in psychological interventions and marital counseling programs to reduce stress levels in married couples.